Peppermint Terhadap Mual Muntah Pada Ibu Hamil Trimester I Di Wilayah Kerja Puskesmas Salam Babaris - Muntianah, Siti; Meldawati, Meldawati; Mardiatul Ulfa , Ika (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Nausea and vomiting occur in pregnant women in the first and second trimesters and can last up to 4 months. The impact can be experiencing disruption in work, household activities, psychological disturbance. Interventions can be carried out non-pharmacologically by using peppermint which can overcome digestive problems because it has a very high fragrance level, a cold, refreshing, strong aroma. The purpose of the study was to determine the effectiveness of giving peppermint to reduce nausea and vomiting in first trimester pregnant women in the working area of the Salam Babaris Health Center, Tapin Regency. The research method uses quasi-experimental types type with one sample test. It was carried out from January to February 2023. The sample consisted of 15 pregnant women. Bivariate analysis using the t test. The results of the study before being given peppermint, 9 people (60%) category of severe nausea vomiting and after being given pappermint became the category of mild nausea vomiting as many as 6 people (40%). The results of the t test obtained a p-value of 0.003, there is an effect of peppermint administration on reducing nausea vomiting in pregnant women trimester I. Giving peppermint in the form of candy is able to overcome nausea vomiting in pregnant women trimester I.